Evaluation of plastic energy dissipation capacity of steel beams suffering ductile fracture under various loading histories. - Jiao, Yu (Earthquake engineering & structural dynamics.)
The energy dissipation capacity of a structure is a very important index that indicates the structural performance in energy-based seismic design. This index depends greatly on the structural components that form the whole system. Owing to the wide use of the strong-column weak-beam strength hierarchy where steel beams dissipate the majority of earthquake input energy to the structures, it is necessary to evaluate the energy dissipation capacity of the beams. Under cyclic loadings such as seismic effects, the damage of the beams accumulates. Therefore, loading history is known to be the most pivotal factor influencing the deformation capacity and energy dissipation capacity of the beams. Seismic loadings with significantly different characteristics are applied to structural beams during different types of earthquakes and there is no unique appropriate loading protocol that can represent all types of seismic loadings. This paper focuses on the effects of various loading histories on the deformation capacity and energy dissipation capacity of the beams. Cyclic loading tests of steel beams were performed. In addition, some experimental results from published tests were also collected to form a database. This database was used to evaluate the energy dissipation capacity of steel beams suffering from ductile fracture under various loading histories.